(untitled) (UNIZIK Journal of Marketing, 2024)
This study examined the impact of fiscal policy on stock market performance in Nigeria from 1999 to 2023. Utilizing secondary data from the national bureau of statistics Annual bulletin, the study analysed the effects of government spending, taxation policies, and government borrowing on the stock market. The Ordinary Least Squares (OLS) regression method was employed to determine the relationship between these fiscal policy variables and stock market performance. The findings revealed that government spending has a statistically significant positive relationship with stock market performance, accounting for 64.8% of the variability (R² = 0.648, p < 0.05); the government taxation policies statistically significant effect on stock market performance accounts for 52.1% of the variability (R² = 0.521, p < 0.05); the government borrowing significantly influence stock market performance in Nigeria at 75.6% (R² = 0.75.6, p < 0.05). Government spending positively impacts the stock market by stimulating economic activities, while favourable taxation policies enhance investor confidence and market trends. Conversely, excessive government borrowing can negatively affect the stock market due to higher interest rates and crowding out of private investment. Effective fiscal policy tools are shown to promote long-term growth and stability in the stock market. The findings revealed that government spending has a statistically significant positive relationship with stock market performance, accounting for 64.8% of the variability (R² = 0.648, p < 0.05).". Based on these findings, it is recommended that the Nigerian government adopts prudent fiscal policies to foster a conducive investment environment and stimulate stock market performance.